2017
DOI: 10.1016/j.tra.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Examining usage patterns of a bike-sharing scheme in a medium sized city

Abstract: Bike-sharing is one of the fastest growing new modes of transport in the world, with more and more schemes coming online every year. This paper examines the trends in a bike-sharing scheme that has been in operation in Cork since 2014. While many studies exist on how bike-sharing schemes are changing mobility in cities across the globe, few studies have looked and the dynamics of these schemes in smaller cities. The findings of this research show that in a small compact city like Cork the average trip times re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 22 publications
5
69
0
5
Order By: Relevance
“…Shared bicycles are one of the fastest growing modes of shared mobility and have been increasing in popularity worldwide in recent years. By the end of 2017, more than 23 million shared bicycles were available around the globe and 304 cities in more than 20 countries had implemented bicycle-sharing systems [19]. In 2017, there were more than 20 million shared bicycles in China and 22.1 Journal of Advanced Transportation 3 million subscribers [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shared bicycles are one of the fastest growing modes of shared mobility and have been increasing in popularity worldwide in recent years. By the end of 2017, more than 23 million shared bicycles were available around the globe and 304 cities in more than 20 countries had implemented bicycle-sharing systems [19]. In 2017, there were more than 20 million shared bicycles in China and 22.1 Journal of Advanced Transportation 3 million subscribers [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently, Faghih-Imani and Eluru found that users' destination preferences significantly affected cycling choices [26]. De Chardon et al found that station-based systems encountered constraints in relation to the maximization of profits and service levels [27], although these constraints could be relaxed in medium-sized cities [28]. Moreover, Faghih-Imani et al concluded that bike-sharing systems were likely to be favoured where urban congestion was serious [29].…”
Section: Station-based Systemsmentioning
confidence: 99%
“…One of the largest bike-sharing companies was Yonganxing. In 2014, it provided services in over 200 mainly small and medium sized cities, proving that station-based systems could be successful in cities of these sizes [28]. In these cities, a finite number of stations could meet cycling demand.…”
Section: Launch Of Bike-sharing Systemsmentioning
confidence: 99%
“…In general, compared with SC data, bicycle trip data lacks card ID and thus cannot be used to model users' travel behavior. By far, public bicycle SC data has been used to investigate public bicycle users' travel patterns [22] as well as bicycle trip chains for men and women [14,23]. Public bicycle SC data could also help to classify different types of behaviors and compare the trip disparity [24].…”
Section: Smart Card Data For Trip Chainmentioning
confidence: 99%